POLICY IMPLEMENTATION OF REMEDIAL MEASUREMENT TO ASSIST SME’S BUSINESS AFFECTED BY THE COVID-19 SITUATION - Atsawasriworanan, Somsak; Kalyanamitra, Kamolporn; Niyomyaht, Satit; Lakkanapichonchat, Tassanee (Journal of Educational Review Faculty of Education in MCU, 2021)
The purpose of this research was to 1) to study the policy implementation of remedial measurement to assist the SMEs business affected by the COVID-19situation. and 2) to study the problems and obstacles in policy implementation of remedial measurement to assist the SMEs business affected by the COVID-19 situation. This research was qualitative by collecting from interviews with 18 key informants who wereexecutives in the public and private sectors involved in SMEs consisted of government policymakers, SME’s business association by purposive selection, the tools used for data collection were structured interviews. The results of the study concluded that: 1) Policy implementation of remedial measurement to assist the SMEs business affected by the COVID-19situation: (1) The deferral of principal and interest payments by Bank of Thailand: There was a policy for public financial institutions and private sector financial institutions to extend the period of deferring repayment of both principal and / or interest by not more than 6 months. (2) Soft loans: Bank of Thailand had allocated soft loans to private financial institutions to lend to SMEs. (3) Granting of new or additional credit through the state-owned financial institution by providing loans through financial institutions both government and private sectors, through various projects (4) The sound of the operator: There was a joint discussion between government agencies and the private sector on the direct and indirect impacts and barriers of the COVID-19 situation. (5) Speed in issuing measures to keep up with the situation: The government and Bank of Thailand had urgently issued measures in accordance with the Financial Aid Act to assist SMEs affected by COVID-19. (6) Maintaining continuity of measures during the affected period by extending time and extending the amount of measures to assist SMEs in deferring of principal payments, loans through under relentless conditions and releasing new credit to existing or new customers. (7) Cooperation between the public and private sectors in which the public and private sectors cooperated in proceeding with the postponement of principal and interest payments, loans through under relentless conditions, releasing new credit to existing or new customers (8) Problems and obstacles: Some operators were unable to borrow money from financial institutions, needed to borrow money outside the system until being cheated and being taken advantage of, and the rules and regulations were not consistent with the current situation and had many conditions, causing some operators to not receive assistance from government measures.